Pandora's locks : the opening of the Great Lakes-St. Lawrence Seaway - Alexander, Jeff, 1962- (East Lansing, Mich. : Michigan State University Press, 2009)
The St. Lawrence Seaway was considered one of the world''s greatest engineering achievements when it opened in 1959. The 1 billion project-a series of locks, canals, and dams that tamed the ferocious St. Lawrence River-opened the Great Lakes to the global shipping industry. Linking ports on lakes Superior, Michigan, Huron, Erie, and Ontario to shipping hubs on the world''s seven seas increased global trade in the Great Lakes region. But it came at an extraordinarily high price. Foreign species that immigrated into the lakes in ocean freighters'' ballast water tanks unleashed a biological.
PROLOGUE: Death of an icon -- DOMINION: Conquering nature -- Vampires of the deep -- Salt in the wound -- Alewife invasion -- A king is born -- PLAGUE: Fatal error -- Dangerous cargo -- Reckoning -- Ruffe seas -- Smoke and mirrors -- Meltdown -- DREISSENA EFFECT: Something amuck -- Blue, green, and deadly -- Cruel hoax -- Caspian Sea diet -- Whitefish and green slime -- Paradox -- Fear this -- BETRAYAL: Dirty secrets -- Who's in charge? -- Mission impossible -- Seaway heretics -- Westward Ho! -- Saving paradise -- EPILOGUE: Hope amid the ruins.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
JSTOR
Keywords: Biological invasions -- Great Lakes (North America); Nonindigenous aquatic pests -- Great Lakes (North America); Discharge of ballast water -- Environmental aspects -- Saint Lawrence Seaway; Discharge of ballast water -- Government policy -- North America; Nonindigenous aquatic pests -- Control -- Great Lakes (North America); Invasions biologiques -- Grands Lacs (Amérique du Nord); Animaux et plantes nuisibles aquatiques non indigènes -- Grands Lacs (Amérique du Nord); Déballastage -- Aspect de l'environnement -- Voie maritime du Saint-Laurent.; Déballastage -- Politique gouvernementale -- Amérique du Nord; Animaux et plantes nuisibles aquatiques non indigènes -- Lutte contre -- Grands Lacs (Amérique du Nord); HISTORY -- United States -- State & Local -- Midwest (IA, IL, IN, KS, MI, MN, MO, ND, NE, OH, SD, WI); Biological invasions; Discharge of ballast water -- Environmental aspects; Nonindigenous aquatic pests; Nonindigenous aquatic pests -- Control; Great Lakes; North America; North America -- Saint Lawrence Seaway; Aquatisches Ökosystem; Ballasttank; Invasion; Umweltkatastrophe; Große Seen